Efficacy of double filtration plasmapheresis in the treatment of steroid and/or IVIG unresponsive neuronal surface antibodies associated autoimmune encephalitis - Xiaowan Liang; Chen Zhang; Jun Xue; Yin Zheng (BMC Neurology)
Abstract Introduction Whether double filtration plasmapheresis (DFPP) is effective in the patients who do not response to the initial immunotherapy is uncertain. This retrospective study aimed to evaluate the efficacy and safety of DFPP in the treatment of patients who had no improvement after initial immunotherapy (steroids and/or immunoglobulin (IVIG)), and moreover, to investigate the factors associated with the efficacy of DFPP. Methods From January 1st, 2014, to December 30th,2018, a total of 26 patients who were diagnosed autoimmune encephalitis (AE) and were received the treatment of DFPP after unsuccessful or incomplete recovery from their early immune therapy (including intravenous high-dose cortisone, IVIG and or immunosuppressant) for at least 21 days were investigated. Their plasmapheresis volume, the course of disease, treatment sessions, and complications were recorded. The efficacy of DFPP within a week were assessed by modified Rankin scale (mRS). These patients were followed until six months after the last session of DFPP treatment. Results The duration between the onset of symptoms and DFPP administration was 54.5 days (range 21—243 days). The median DFPP sessions for each patient were three (range 2–6 sessions), and the mean volume of plasma exchange was 50.5 ± 11.1 ml/kg/session. Total clinically relevant improvement was observed in 57.7% of the patients. The median mRS was decreased from 5 to 4 within one week after DFPP treatment (P < 0.001). Only one patient relapsed in the following six months after DFPP. The effectiveness of DFPP has no relationship with age, gender, the type of antibody, with or without neoplasm, clinical course and the volume of plasma exchange. Most patients tolerated well, except 2 cases. One encountered mild allergic reaction and the other had a transient hypotension during DFPP treatment, but both were corrected rapidly. Conclusion DFPP is an effective and safe treatment option for patients who have poor responsiveness to early immunotherapy).